Single photon core ionization with core excitation: a new spectroscopic tool. (August 2015) - Penent, F; Carniato, S; Lablanquie, P; Selles, P; Palaudoux, J; Andric, L; Žitnik, M; Bučar, K; Shigemasa, E; Nakano, M; Hikosaka, Y; Ito, K
Synopsis: The simultaneous core ionization and core excitation process (or K -2 V process) induced by absorption of a single photon provides the basis of a new spectroscopy that offers both advantages of X-ray Photoelectron Spectroscopy (XPS) and near-edge x-ray absorption fine structures (NEXAFS) spectroscopy